Relationship of serum calcium level with basal metabolic index & hip circumpherence in obese females of reproductive age - Akter, N; Akhter, AS; Hossain, MZ; Deb, SR; Khan, MH; Shahjadi, S; Begum, R (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10540 J. Dhaka Med. Coll. 2011; 20(2): 141-145